Admissions essay boot camp : how to write your way into the elite college of your dreams - Wellington, Ashley (Berkeley : Ten Speed Press, 2014)
"This top-tier college admissions essay guide replicates a brainstorming and essay-writing session with Mint Tutors founder Ashley Wellington"--
Keywords: College applications -- United States -- Handbooks, manuals, etc; Universities and colleges -- United States -- Admission -- Handbooks, manuals, etc; Exposition (Rhetoric) -- Handbooks, manuals, etc; Essay -- Authorship -- Handbooks, manuals, etc; STUDY AIDS / College Entrance; STUDY AIDS / SAT; STUDY AIDS / Financial Aid; Print books